GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 25 May 2020, 04:33

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 64096
If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =  [#permalink]

### Show Tags

07 Apr 2019, 20:40
00:00

Difficulty:

15% (low)

Question Stats:

93% (00:21) correct 7% (00:53) wrong based on 14 sessions

### HideShow timer Statistics

If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =

(A) 1

(B) 2

(C) 3

(D) 4

(E) 5

Source: Nova GMAT
Difficulty Level: 600

_________________
Intern
Joined: 08 Apr 2018
Posts: 40
Re: If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =  [#permalink]

### Show Tags

07 Apr 2019, 20:54
Since a>0, the only value for a is 3.
a-3=0 hence a=3

Posted from my mobile device
VP
Joined: 31 Oct 2013
Posts: 1489
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =  [#permalink]

### Show Tags

07 Apr 2019, 21:05
Bunuel wrote:
If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =

(A) 1

(B) 2

(C) 3

(D) 4

(E) 5

Given,

(a + 2)(a – 3)(a + 4) = 0

a = -2

a = 3

a = -4

GMAT Club Legend
Joined: 18 Aug 2017
Posts: 6266
Location: India
Concentration: Sustainability, Marketing
GPA: 4
WE: Marketing (Energy and Utilities)
Re: If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =  [#permalink]

### Show Tags

07 Apr 2019, 23:03
Bunuel wrote:
If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =

(A) 1

(B) 2

(C) 3

(D) 4

(E) 5

a=3 sufficient to get relation (a + 2)(a – 3)(a + 4) = 0
IMO C
Re: If (a + 2)(a – 3)(a + 4) = 0 and a > 0, then a =   [#permalink] 07 Apr 2019, 23:03